UBAP2L is amplified in a large subset of human lung adenocarcinoma and is critical for epithelial lung cell identity and tumor metastasis. Issue 11 (28th July 2017) - Aucagne, Romain; Girard, Simon; Mayotte, Nadine; Lehnertz, Bernhard; Lopes‐Paciencia, Stéphane; Gendron, Patrick; Boucher, Geneviève; Chagraoui, Jalila; Sauvageau, Guy
Abstract : The ubiquitin‐associated protein 2–like ( UBAP2L ) gene remains poorly studied in human and mouse development. UBAP2L interacts with the Polycomb group protein B lymphoma Mo‐MLV insertion region 1 homolog (BMI1) and determines the activity of mouse hematopoietic stem cells in vivo . Here we show that loss of Ubap2l leads to disorganized respiratory epithelium of mutant neonates, which die of respiratory failure. We also show that UBAP2L overexpression leads to epithelial‐mesenchymal transition–like phenotype in a non‐small cell lung carcinoma (NSCLC) cell line. UBAP2L is amplified in 15% of human primary lung adenocarcinoma specimens. Such patients express higher levels of UBAP2L and show a reduction in survival when compared with those who do not have this gene amplification. Supporting a possible role for UBAP2L in lung tumor progression, NSCLC cells engineered to express low levels of this gene produce much smaller tumors in vivo than wild‐type control cells. Together, these results suggest that UBAP2L contributes to epithelial lung cell identity in mice and that it plays an important role in human lung adenocarcinoma.—Aucagne, R., Girard, S., Mayotte, N., Lehnertz, B., Lopes‐Paciencia, S., Gendron, P., Boucher, G., Chagraoui, J., Sauvageau, G. UBAP2L is amplified in a large subset of human lung adenocarcinoma and is critical for epithelial lung cell identity and tumor metastasis. FASEB J. 31, 5012–5018 (2017). www.fasebj.org